“Sputtanapoli” from the Library Shelf to the Cinema to the Sofas: the Relationship between Bestseller and Film in the Case of La paranza dei bambini (Altre Modernità, 2025)
This paper aims to investigate the relationship between Roberto Saviano’s novel La paranza dei bambini (2016) and its film adaptation directed by Claudio Giovannesi in 2019, which won the Best Screenplay award at the 69th Berlinale. Following in the footsteps of the renowned bestseller Gomorra (2006), the novel immediately demonstrated its adaptability, as proved by its theatrical adaptation, which premiered at the Nuovo Teatro Sanità in Naples on April 19, 2017. But how does La paranza dei bambini succeed in portraying the connection between teenagers and the Camorra on the page and on the screen (and on stage)? In what ways does the movie contribute to shaping the collective imagination of the criminal underworld? And how does the film succeed in reaching such a diverse audience both in cinemas and via streaming platforms? While the first part of this essay will focus on the novel’s engagement with the criminal imaginary and its connection to Saviano’s debut work Gomorra, the second part will examine the dialogue between the novel and the screenplay, exploring stylistic and thematic peculiarities, recurring motifs, similarities, and differences.
Keywords: criminal underworld imagery; cinematic adaptation; Roberto Saviano; Claudio Giovannesi; screenplay